Modeling the measurement of carbon dioxide removal: perspectives from the philosophy of measurement - Wilson, Joseph (Frontiers in Climate, 2024)
This paper explores how recent developments in the philosophy of measurement can frame and guide the way we measure successful carbon sequestration in carbon dioxide removal (CDR) projects. Recent efforts to mitigate carbon emissions, e.g., the forest offset program implemented in California, have been revealed to systematically over-credit projects relative to the benefits they produce for the climate. In this paper I utilize concepts from the philosophy of measurement, primarily those surrounding models of the measurement process, to diagnose this problem of over-crediting in the broader context of concerns about uncertainty and impermanence in CDR. In light of these measurement models, I argue for absolute measurement targets in favor of the standard comparative targets, the latter of which are significantly dependent on tenuous baseline projections. I go on to consider which contemporary approaches to CDR are successful in light of lingering future uncertainty, which puts particular emphasis on the permanence of carbon sequestration. Independent of the specific argument developed here, the paper also serves to introduce concepts from the philosophy of science and measurement to a broader audience, in the hopes they will benefit other areas of research.